Between Da’wah and Politics: A Study on the Role and Local Political Participation of Muslimat Nahdlatul Ulama - Mutrofin, Mutrofin; Ni’amah, Luthfi Ulfa; Styawan, Fajar Haris; Pratiwi, Clara Sinta (Islamic Management and Empowerment Journal, 2026)
This study aims to analyze the involvement of Muslimat NU actors in the political sphere as a strategic issue that has attracted significant attention from academics, activists, and policymakers. The low representation of women in legislative institutions is not merely a numerical problem but also concerns the substantive dimension of democracy itself. This research employs a qualitative approach, with primary data collected directly from the field. Data collection methods include observation, interviews, and documentation. The findings reveal the roles played by Muslimat NU women in both religious outreach (dakwah) and political activities, the challenges they face when these two domains intersect—particularly during electoral contestations—and the strategies they develop to navigate conflicts of loyalty between religious organizational commitments and political party affiliations. The study highlights that while dakwah remains a visible and official mandate of the organization, political engagement often operates more subtly, yet leaves a tangible impact on the dynamics of local democracy.